A selective alkaline etching strategy to prepare hierarchical Beta molecular sieves for the hydrodeoxygenation of phenol. (15th February 2023) - Yu, Hai; Guo, Delin; Hao, Wenfeng; Li, Zitong; Jiang, Wenlong; Li, Lu; Wang, Xiaosheng; Subhan, Fazle; Song, Zhanqian; Liu, Yuxiang
Highlights: Partial distribution and size of mesopores in Beta molecular sieves are controllable regulated. Synergistic mechanism of CTAB and NaOH is fabricated by identifying the role of CTAB molecules in the chemical etching process. Dispersion of supported metallic sites on Beta molecular sieves are improved due to the uniformly distributed mesopores. Abstract: A selective alkaline etching strategy is reported to prepare hierarchical Beta molecular sieves with cetyltrimethyl ammonium bromide (CTAB). The homogeneity of mesopores is tuned by surface modification of Beta molecular sieves. CTAB selectively interacts with crystal defects and protects primary etched small mesopores from continuous destruction to form large mesopores. Under the synergistic effect of NaOH solution and CTAB, the acidity retention of Beta molecular sieves is higher due to the removal of Si(OSi)4 rather than Si(OSi)3 (OAl) species. When employed as the support of Pt/Beta catalysts, hydroxyl adsorption of phenol on Beta molecular sieves and Pt particles are observed. Dispersion of Pt on the surface of Beta molecular sieves is improved due to the uniform distribution of mesopores. A higher dispersion of Pt attributes to a higher deoxygenation conversion of phenol. The unique contribution of the current research is to propose the role of CTAB in alkaline etching process, realizes the controllable porosity regulation, and alleviates the acidity loss of Beta molecular sieves. These results are important to broaden the application fields of aluminum–silicon molecular sieves especially for large molecules engaged reactions and preparation of supported catalysts with a high metal dispersion.